Crucial workload variables in female-male elite Brazilian Beach Handball: An exploratory factor analysis - Gómez-Carmona, Carlos D.; Rojas-Valverde, Daniel; Rico-González, Markel; De Oliveira, Vinicius; Lemos, Luis; Martins, Clarice; Nakamura, Fábio; Pino-Ortega, José (Biology of Sport, 2023)
This study aimed to identify the most important variables of male and female beach handball workload demands and compare them by sex. A total of 92 elite Brazilian beach handball players (54 male: age 22.1±2.6 years, height 1.8±0.5 m, weight 77.6±13.4 kg; and 38 female: age 24.4±5.5 years, height 1.7±0.5 m, weight 67.5 ± 6.5 kg) were analyzed in 24 official matches during a four-day congested tournament. From 250 variables measured by the inertial measurement unit, fourteen were extracted for analysis using Principal Component Analysis as selection criteria. Five Principal Components (PC) were extracted that explained 81.2–82.8% of total variance (overview of workload demands during beach handball). Specifically, 36.2–39.3% was explained by PC1 (DistanceExpl, Distance, Distance4–7km/h, and Acc), 15–18% by PC2 (AccMax, Acc3–4m/s, Dec4–3m/s), 10.7–12.9% by PC3 (JumpsAvg Take-Off, JumpsAvg Landing and PLRT), 8–9.4% by PC4 (Distance > 18.1km/h, SpeedMax), and 6.7–7.7% by PC5 (HRAvg and Step Balance). Sex-related differences were found in the PC distribution of variables, as well as in selected variables(HRAvg,Dec4–3m/s, Acc3–4m/s, JumpsAvg Take-Off, JumpsAvg Landing, AccMax, Distance, Distance4–7km/h, Acc, SpeedMax) with higher values in male players (p < .05). In conclusion, the sex-related PC distribution and workload demands in beach handball should consider for training design and injury prevention programs.